2021
DOI: 10.1038/s42003-021-02751-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying spatio-temporal seizure propagation patterns in epilepsy using Bayesian inference

Abstract: Focal drug resistant epilepsy is a neurological disorder characterized by seizures caused by abnormal activity originating in one or more regions together called as epileptogenic zone. Treatment for such patients involves surgical resection of affected regions. Epileptogenic zone is typically identified using stereotactic EEG recordings from the electrodes implanted into the patient’s brain. Identifying the epileptogenic zone is a challenging problem due to the spatial sparsity of electrode implantation. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…VEP uses personalized brain network models and machine learning methods by integrating epilepsy patient‐specific anatomical with functional data to provide a computational representation of the hypothesized epileptogenic and propagation zone networks in cerebral space. This method has recently been validated by modeling seizures previously recorded in SEEG 24,29 and on synthetic data 30,31 . The pilot study by Proix et al 29 further showed that VEP can reliably predict seizure propagation, suggesting that in the future this approach could improve SEEG analysis and consequently surgical prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…VEP uses personalized brain network models and machine learning methods by integrating epilepsy patient‐specific anatomical with functional data to provide a computational representation of the hypothesized epileptogenic and propagation zone networks in cerebral space. This method has recently been validated by modeling seizures previously recorded in SEEG 24,29 and on synthetic data 30,31 . The pilot study by Proix et al 29 further showed that VEP can reliably predict seizure propagation, suggesting that in the future this approach could improve SEEG analysis and consequently surgical prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of recent advances in probabilistic programming languages (PPLs) for automatic Bayesian inference such as Stan (a state-of-the-art platform for statistical modeling), the feasibility of inverting the coupled Epileptor model that best explains patient's data from whole-brain source activity has been shown previously (Hashemi et al, 2020(Hashemi et al, , 2021. In other studies, efficient and robust inversion of seizure propagation on whole-brain intracranial recordings were achieved by either simplifying the seizure dynamics using a threshold model (Sip et al, 2021) which considerably restricts the range of model dynamics, or by embedding Epileptor equations as priors on brain source dynamics and using maximum a posteriori (MAP) techniques, which does not capture the uncertainty in parameters (Vattikonda et al, 2021). These issues could possibly be addressed by sampling the whole posterior of Epileptor parameters using gradient-based and self-tuning MCMC sampling algorithms such as No U-Turn sampler (NUTS; Hoffman and Gelman (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…These issues could possibly be addressed by sampling the whole posterior of Epileptor parameters using gradient-based and self-tuning MCMC sampling algorithms such as No U-Turn sampler (NUTS; Hoffman and Gelman (2014)). However, MCMC sampling of the posterior density from sparse observations such as SEEG recordings becomes computationally infeasible, in particular when parameters in a high-dimensional model such as VEP show strong non-linear correlations or if the posterior exhibits pathological geometries such as Neal’s funnel with varying curvature (Betancourt et al, 2014; Vattikonda et al, 2021). Recently, a hybrid of NFs (such as inverse autoregressive flows parameterized by neural networks) and HMC called neural-transport (NeuTra) HMC (Hoffman et al, 2019) has been proposed to correct this sort of unfavorable geometry, while it works in the amortized setting.…”
Section: Discussionmentioning
confidence: 99%
“…This dual approach guides the identification of causal mechanisms, going beyond the estimation of statistical correlations in traditional data mining approaches. Examples include the Perturbation Complexity Index (PCI) used to assess effective connectivity ( Comolatti et al, 2019 ), variants of dynamic causal modeling used in The Virtual Brain (TVB; see below for examples of clinical applications) and uses of generative models in a “digital twin” approach ( Hashemi et al, 2020 ; Vattikonda et al, 2021 ), which optimizes parameters to best explain personalized data as a prelude to characterizing within and between subject variability.…”
Section: Brain Complexitymentioning
confidence: 99%
“… TVB, a data-driven neuroinformatics tool, fusing individual brain imaging data with atlas data and state-of-the-art brain modeling, for personalized simulations of brain activity and clinical interventions. Generative brain models operationalize a causal hypothesis, which is evaluated against the patient’s own brain imaging data using variants of dynamical causal modeling such as Monte Carlo simulations ( Hashemi et al, 2020 , 2021 ; Sip et al, 2021 ; Vattikonda et al, 2021 ; https://www.humanbrainproject.eu/en/medicine/the-virtual-brain/ ). …”
Section: The Role Of Modeling and Simulation In Diagnosis And Therapymentioning
confidence: 99%